Effects of crystallization temperature and cooling rate on the polymorphism of trans‐1, 4‐polyisoprene vulcanizate. Issue 47 (12th October 2022) - Wang, Wenjun; Yu, Xinyu; Xia, Mingchen; Wang, Dongdong; Wu, Jinghua; Hu, Jian; Yan, Shouke; Xue, Meiling
Abstract: The effects of crystallization temperature and cooling rate on the polymorphism of trans ‐1, 4‐polyisoprene vulcanizate (TPI‐V) with different sulfur dosages were monitored by WAXD in real time. The results showed that both the crystallization temperature and the cooling rate play decisive roles in determining the polymorphism and their relative amounts, whereas their effects are interfered by the crosslinking density which restrains the crystallization kinetics. Only α crystal is formed when crystallization is conducted at 40°C or greater and mixed α / β crystals are obtained in the temperature range of 10–30°C. β crystal is predominate when crystallized at 10°C while α crystal is limited at 30°C. Both the lower temperature and increased crosslinking density are beneficial to β crystal formation. A high crosslinking density causes a prolonged time is needed for pure α crystal formation, and hinders the TPI‐Vs from forming pure α crystal even if crystallization is conducted at 45°C. A lower cooling rate favors the formation of α crystal while a higher cooling rate favors β crystal formation. The β spherulites are much brighter than α spherulites under the observation of polarized microscopy. Abstract : The crystallization temperature, cooling rate and crosslinking density all influence the polymorphism of trans ‐1, 4‐polyisoprene vulcanizate (TPI‐V). Only α crystal is formed when isothermally crystallized at 40°C or greater, and mixed α / β crystals are obtained in the temperature range of 10–30°C. The lower crystallization temperature, higher cooling rate and increased crosslinking density are all beneficial to β crystal formation.